2021
DOI: 10.1055/s-0041-1729778
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous CT Guided Vertebral Biopsy: Anatomy and Technical Considerations

Abstract: In this review article, the authors discuss the anatomy and technical aspects of CT-guided biopsy of vertebral lesions. CT guidance is highly useful for vertebral biopsies, as the anatomy of the spine is complex and varies widely across the levels. Prebiopsy imaging should be reviewed and later correlated with the final histopathological diagnosis. The majority of the spine biopsies are performed under local anesthesia, except those in critical locations and pediatric age groups. The biopsy sample is sent for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…It is not clear whether these complications were due to the severe osteolysis and the expected progression of the infection after diagnosis, or to the FNB and TCB procedure. The low rate of complications (9%) agrees with the human literature, where complications after spinal CT-guided percutaneous sampling are in the range of 0-10% and less frequent than after surgical procedures [15,27].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is not clear whether these complications were due to the severe osteolysis and the expected progression of the infection after diagnosis, or to the FNB and TCB procedure. The low rate of complications (9%) agrees with the human literature, where complications after spinal CT-guided percutaneous sampling are in the range of 0-10% and less frequent than after surgical procedures [15,27].…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the size of the needle used was 22 G. Small needle sizes (22 G and 20 G) have been used in other studies in small animals and people because it prevents contamination of the sample with blood [7,22,[25][26][27][28]. The nature of the lesions (size, shape and location) prevented from taking complementary TCBs in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Gala et al 16 found CT-guided percutaneous biopsy is safer than open surgical biopsy with lower rates of complications and shorter hospital stays.…”
Section: The Coaxial Graded Needle Exchange Technique Described Ensur...mentioning
confidence: 99%